Experimental and Numerical Investigation of Nanofluid Usage in a Plate Heat Exchanger for Performance Improvement - Sözen, Adnan; Khanları, Ataollah; Çiftçi, Erdem (International Journal of Renewable Energy Development, 2019)
Plate heat exchangers, a compact-type heat exchanger, are commonly used heat transfer devices because of their superior characteristics. Their thermal performances are strongly dependent to working fluid circulating inside the system. The influences of nanofluid utilization as the working fluid in a plate heat exchanger was experimentally and numerically analysed in this study. In order to show off the improvement rate in heat transfer, the experiments were performed by using deionized water and TiO2-deionized water nanofluid. The nanofluid was prepared at the rate of 1.5 % as weighted. A surface-active agent, Triton X-100, was also doped into the mixture at the rate of 0.2% of a final concentration to prevent the sedimentation and flocculation of the nanoparticles inside the solution. The experiments were performed in different temperatures as 40°C, 45°C, 50°C and varying cold fluid mass flow rates as 3,4, 5, 6 and 7 lpm.  In addition, using the experimental data, a numerical simulation was realized by ANSYS Fluent software.  The both results indicate that heat transfer rate in plate heat exchanger can be improved using nanofluid as the working fluid in place of deionized water. The maximum improvement rate in heat transfer was obtained as 11 % in experimental study. It is also seen that experimental and numerical results are in good agreement.©2019. CBIORE-IJRED. All rights reservedArticle History: Received May 18th 2018; Received in revised form October 17th 2018; Accepted January 8th 2019; Available onlineHow to Cite This Article: Sözen, A., Khanlari, A., and Çiftçi, E. (2019) Experimental and Numerical Investigation of Nanofluid Usage in a Plate Heat Exchanger for Performance Improvement. Int. Journal of Renewable Energy Development, 8(1), 27-32.https://doi.org/10.14710/ijred.8.1.27-32